KETIDAKPATUHAN PENDERITA DIABETES DALAM MENJALANI PENGOBATAN (Studi Kasus Di Desa Kaligayam Kecamatan Talang Kabupaten Tegal) (Intuisi : Jurnal Psikologi Ilmiah, 2009)
The research is aimed to find out what are the factors that influenced non adherence of diabetics regiment behavior, to find out the kinds of non adherence diabetics behavior, and to find out what is the reason that caused diabetics does not adherence to take a medical treatment. The subjects of this research were 2 people; they are diabetics, who do not have adherence behavior to experiencing medication, they are more than 50 years old, and have suffered from diabetes for more than 3 years. The data were collected with 3 methods that are observation and interview methods and psychological testing (DAM), and tested with interview and observation result transcript analysis, and interpretation of psychological test result. Based on the result, there are 7 factors that influencing non adherence behavior of diabetics on taking the medical treatments, they are patients have wrong understanding of diabetes experrancing disease, lack of knowledge about a risk if impinge the treatment regiment (medication), difficulties of communication between the doctor and patients, the wrong belief and perception about the disease, family and social (significant others) supports, attitude towards health treatment system, and individual characteristic of the patients, The result of research also shows that kinds of non adherence behavior of diabetics on experiencing treatment regiment (medication) can be seen from 5 matters, they are the irregular schedule of doctor control, stopping consuming medicine that not following the rules, impinge the rules of eat pattern which doctor has suggested, irregular exercise, and irregular and even undone bloods sugar levels checking. The reasons of non adherence diabetics on experiencing treatment regiment (medication), they are abundant trust of traditional medicine, feeling slack and tire feeling of the patient, bad communication between doctor and patients. Also, the diabetics personality such as less confidence level tendencies, less acceptance of challenge and reality, and unstable emotional condition influence a non adherence diabetic 's behavior in experiencing treatment regiment (medication).